IUD Insertion Video: A Versatile Teaching and Evaluation Module - Juan Garcia-Rodriguez (Association of American Medical Colleges, 2015)
Abstract Introduction This video module is an effective and versatile teaching tool that provides comprehensive instruction for intrauterine device (IUD) insertion in any clinical setting or academic situation. This method was created to offer an alternative for IUD insertion training due to the difficulties faced by medical learners, particularly family medicine residents, to obtain the required training. The method is simple to implement, provides easier access than the traditional methods of instruction for learners (i.e., demonstration and instruction in IUD insertion clinics), and reduces time for instruction and evaluation by preceptors. Methods This resource has three components: the video, the written material for instruction, and a validated measurement instrument. The effectiveness of the video module was studied in a group of 39 learners, comparing it with the traditional form of instruction. Results The results showed that the video module is as effective as the traditional method of instruction in providing procedural knowledge instruction. In procedure performance, the video module group performed better than the traditional group. The pretest and the posttest were compared to assess whether the intervention influenced knowledge within the groups. In the traditional instruction group, the participants improved significantly from the beginning to the end of the study, pretest (M = 8.0, SD = 2.52) and posttest (M = 11.3, SD = 1.70, t(18) = 5.64, p < .5). The group exposed to the video-module instruction also demonstrated a significant improvement in knowledge, pretest (M = 9.0, SD = 2.33) and posttest (M =12.3, SD = 1.87, t(19) = 6.92, p < .05). The participants in the video module instruction group obtained higher scores (M = 48.1, SD = 4.89) than the participants in the traditional instruction group (M = 43.8, SD = 6.42, t(37) = 2.37, p < .05). The between groups effect size difference was in favor of video module training with a medium effect size difference compared to the traditional training approach (d = 0.75). Discussion This video-module is an alternative to traditional forms of instruction that aims to overcome the difficulties faced by learners to obtain procedural training in IUD insertion. The video-module is being used at the University of Calgary Family Medicine Department in regular scheduled curricular activities for first-year residents and students, and is being implemented for its use by faculty and community preceptors in clinical urban and rural settings.